Filsafat Perenial dan Dialog Agama: Studi Pemikiran Seyyed Hossein Nasr - Wahyuni, Dwi; Fauzi Harlis Yurnalis, Syukri Al; Idris, Mhd (JURNAL AL-AQIDAH, 2021)
Social conflict as something that no longer only stems from the issue of economic inequality and political interests. However, differences in conceptions between religions and religious prejudice against other religious communities are the causes of social conflicts. The important thing that urgently needs to be done is to create and expand religious dialogue. However, the religious dialogue that has been initiated and practiced over the last few decades still needs to be taken more seriously. This study aims to complete a literature review related to how perennial philosophy can be an alternative approach to a more serious religious dialogue. This study focuses on the thoughts of Seyyed Hossein Nasr several of his works that are relevant to discussions related to perennial philosophy and religious dialogue. The research method was carried out by collecting data using library research techniques. After the data has been collected, then data analysis is carried out using historical descriptive methods. The results of this study indicate that Seyyed Hossein Nasr's perennial philosophy offers an attitude that allows religious dialogue to be more serious and fruitful. With Seyyed Hossein Nasr's perennial philosophy, dialogue is carried out with clear integrity and genuine openness for mutual understanding to take place. Integrity and openness to dialogue with existing differences contribute to understanding differences in conceptions and breaking down prejudices between religious believers.